Fluorinated Poly‐oxalate Electrolytes Stabilizing both Anode and Cathode Interfaces for All‐Solid‐State Li/NMC811 Batteries. (6th July 2021) - Sun, Han; Xie, Xiaoxin; Huang, Qiu; Wang, Zhaoxu; Chen, Kejun; Li, Xiaolei; Gao, Jian; Li, Yutao; Li, Hong; Qiu, Jieshan; Zhou, Weidong
Abstract: The relatively narrow electrochemical steady window and low ionic conductivity are two critical challenges for Li + ‐conducting solid polymer electrolytes (SPE). Here, a family of poly‐oxalate(POE) structures were prepared as SPE; among them, POEs composed from diols with an odd number of carbons show higher ionic conductivity than those composed from diols with an even number of carbons, and the POE composed from propanediol (C5‐POE) has the highest Li + conductivity. The HOMO (highest occupied molecular orbital) electrons of POE were found located on the terminal units. When using trifluoroacetate as the terminating unit (POE‐F), not only does the HOMO become more negative, but also the HOMO electrons shift to the middle oxalate units, improving the antioxidative capability. Furthermore, the interfacial compatibility across the Li‐metal/POE‐F is also improved by the generation of a LiF‐based solid‐electrolyte‐interlayer(SEI). With the trifluoroacetate‐terminated C5‐POE (C5‐POE‐F) as the electrolyte and Li + ‐conducting binder in the cathode, the all‐solid‐state Li/LiNi0.8 Mn0.1 Co0.1 O2 (NMC811) cells showed significantly improved stability than the counterpart with poly‐ether, providing a promising candidate for the forthcoming all‐solid‐state high‐voltage Li‐metal batteries. Abstract : A family of F‐terminated poly‐oxalate structures were prepared, in which the odd‐carbon‐diol precursors endow higher Li + conductivity. The terminal trifluoroacetate units not only help to generate a LiF‐based passivating layer with the Li‐metal anode, but also improve the antioxidative capability, with which the cycling performance of the all‐solid‐state Li‐metal/NMC811 cells was significantly improved.